Pregnancy loss: Consequences for mental health - Cuenca, Diana (Frontiers in Global Women's Health, 2023)
Pregnancy loss, in all its forms (miscarriage, abortion, and fetal death), is one of the most common adverse pregnancy outcomes, but the psychological impact of such loss is often underestimated. The individual response to this outcome may vary between women—and could be influenced by age, race, culture, or religious beliefs—but most experience anxiety, stress, and symptoms of depression. Because pregnancy loss is not uncommon, health providers are used to dealing with this diagnosis, however the correct management of the process of diagnosis, information-gathering, and treatment can greatly ameliorate the adverse mental consequences for these women. The aim of this review is to examine the different types of pregnancy loss, and consider how each can influence the mental health of the women affected and their partners—in both the short- and long-term; to review the risk factors with the aim of identifying the women who may be at risk of consequential mental health problems; and to provide some advice for health providers to help these women better cope with pregnancy loss. Finally, we provide some points for health providers to follow in order to aid the management of a pregnancy loss, particularly for spontaneous, induced, or recurrent miscarriage, or stillbirth.